Medicamentos Look-Alike, Sound-Alike Um Velho Conceito Sempre em Atualização - Godinho, Liliane Fernandes; Carreira, Cláudia; Martins, Conceição (Journal of the Portuguese Society of Anesthesiology, 2018)
Medicamentos Look-Alike, Sound-Alike Um Velho Conceito Sempre em Atualização